The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.fertnstert.2010.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Extent of acupuncture practice for infertility in the United Kingdom: experiences and perceptions of the practitioners

Abstract: A minority of acupuncturists have become specialists in supporting fertility issues. The use of an acupuncture protocol is common but does not conform to traditional acupuncture as it is taught and practiced for other conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
(20 reference statements)
3
24
0
2
Order By: Relevance
“…Acupuncture for infertility has increased five-fold over the past decade (Macpherson et al 2006). In a questionnaire survey of 861 acupuncture practitioners, 15% reported that fertility patients have become a substantial proportion of their practice, and the majority were related to assisted conception (Bovey et al 2010). The majority of the acupuncturists offering mainly private treatment were physiotherapists, nurses or doctors.…”
Section: Prevalence Of Use Of Acupuncture In Ivfmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture for infertility has increased five-fold over the past decade (Macpherson et al 2006). In a questionnaire survey of 861 acupuncture practitioners, 15% reported that fertility patients have become a substantial proportion of their practice, and the majority were related to assisted conception (Bovey et al 2010). The majority of the acupuncturists offering mainly private treatment were physiotherapists, nurses or doctors.…”
Section: Prevalence Of Use Of Acupuncture In Ivfmentioning
confidence: 99%
“…However, not all practitioners off ering acupuncture to these vulnerable infertile women have the appropriate qualifi cation in acupuncture and fertility (Bovey et al 2010). Th is raises the question -should someone off er such treatment without specialist training?…”
Section: Prevalence Of Use Of Acupuncture In Ivfmentioning
confidence: 99%
“…Um die Wirksamkeit von reproduktionsmedizinischen Behandlungsverfahren zu erhöhen und deren oben genannte Belastungen zu mindern, werden in Reproduktionszentren häufig adjuvante Therapieverfahren wie beispielsweise die Akupunktur in die Fertilitätsbehandlungen miteinbezogen [11]. 2002 wurde von Paulus et al [12] die erste klinische Studie über Akupunkturbehandlung als adjuvante Methode zu IVF/ICSI veröffentlicht [13]. Diese randomisierte kontrollierte Studie (RCT) zeigte eine signifikante Verbesserung der Schwangerschaftsrate (SR) bei Patientinnen mit Akupunkturbehandlungen kurz vor und nach dem Embryotransfer (ET) [12].…”
Section: Modalities Of Acupuncture Treatments In Assisted Reproductivunclassified
“…In Anbetracht dessen, dass das Studiendesign eines RCTs primär darauf ausgerichtet ist, eine hohe interne Validität der Studienergebnisse sicherzustellen, um die experimentelle Wirksamkeit einer (27,3%) oder anhand semi-standardisierten Verfahren unter Berücksichtigung von sowohl der individuellen TCM-Diagnose als auch von vorgegebenen Punkteprotokollen bestimmt. Die häufige Anwendung von standardisierten Punkteprotokollen ist möglicherweise darauf zurückzuführen, dass Akupunktur-Leistungserbringende in Fertilitätszentren darauf angewiesen sind, einen entsprechenden Patientendurchlauf zu gewährleisten, oder sich gar vertraglich zur Anwendung von standardisierten Punkteprotokollen verpflichten müssen [13]. Am häufigsten wird Körperakupunktur mit Nadelstimulierung angewendet (84,8%), die in einigen Kliniken durch Ohrakupunktur (24,2%) …”
Section: Erfassung Der Rctsunclassified
“…7 Clinical trials from different countries indicate that acupuncture may improve reproductive function. [8][9][10][11][12][13][14][15] However, these acupuncture trials provide insufficient evidence to determine the effectiveness of acupuncture to induce ovulation or treat infertility in PCOS because of failure to report important clinical outcomes such as live birth and limitations in quality and precision. 6 Methodological problems include small sample size and insufficient information on allocation concealment.…”
mentioning
confidence: 99%